PREPERATION OF ETHANOLIC CRUDE EXTRACTS FROM SEAGRASS OF CYMODOCEA SERRULATA AND THEIR ANTI-COAGULANT PROPERTIES - Tania Michael, Dr. Abirami Arthanari, Dr. Sivaperumal (Chelonian Research Foundation, 2023)
Introduction:The extraction of ethanolic crude extracts from Cymodocea serrulata, a type of seagrass, is essential for exploring its potential anti-coagulant properties. Seagrasses are known for their rich phytochemical content, making them a promising source for bioactive compounds. Understanding the anti-coagulant properties of these extracts can contribute to the development of novel therapeutic agents for clotting disorders and related medical conditions. Aim:To investigate the anti-coagulant properties of seagrass og cymodocea serrulata from preperation of ethanolic crude extracts Materials and methods:Sample of cymodocea serrulata was obtained using ethanolic crude extraction method and Anticoagulant assays such as; prothrombin time and activated partial thromboplastin time were done.GC-MS analysis was also done to examine the bio active compounds of Cymodocea serrulata. Results:The results showed presence of anticoagulant properties present in the sample of Cymodocea serrulata.GC-MS analysis showed the presence of bio active compounds such as;palmitic acid, myristic acid, and pentadecanoic acid as a major component. Conclusion:The findings of this research hold promising implications for the development of new anti-coagulant agents. The seagrass Cymodocea serrulata could serve as a valuable source of natural compounds with anti-coagulant properties. These compounds may have potential applications in the pharmaceutical industry, particularly in the development of novel anti-coagulant drugs or as additives in existing treatments. Keywords:Cymodocea serrulata,anti coagulant property,ethanol crude extract,seagrass.